P222 Multidisciplinary and multiagency working in a metropolitan young people's sexual health clinic. (18th May 2015) - Lindner, Nasiha; Strachan, Katrina; Darvishijazi, Mahasti; Richardson-Jones, Alisa; Edwards, Petal; Phillips, David; Pakianathan, Mark
Abstract : Background/introduction: A weekly multidisciplinary team meeting (MDTM) was introduced to discuss clinically or psychosocially complex cases, facilitate multiagency (MA) working and ensure safeguarding of vulnerable young people accessing services. Aim(s)/objectives: To describe characteristics of young people accessing the service and compare those warranting MDTM or MA input to those in whom this was not required. Methods: Retrospective review of electronic patient records of new patients accessing a young people's clinic (≤18 years) from January to June 2014. Demographics, clinical and psychosocial details, MDTM case note entries or liaison with other agencies including social services, voluntary sector, mental and other health were analysed. Significance calculation: fisher's exact test. Results: 159 cases reviewed. Median age 16 years: female 80%, locally resident 80%, self-referral 77%, white British 22%, black Caribbean 22%. 67(42%) required MA/MDTM working. (45%, n = 30 had MA referral/liaison). MA/MDTM patients were more likely to have health adviser input: 57% vs 21% p = 0.0001, report mental health problems: 33% vs 3% p = 0.0001, have a social worker: 27% vs 7% p = 0.0003 or if female, not on contraception: 60% vs 39% p = 0.005. Amongst those requiring MA/MDTM input 12% (n = 8) had a safeguarding concern and 7% (n = 5) were identified as at risk of sexual exploitation. Discussion/conclusion: MDTMs effectively enabled discussion of complex patients. MDTM/MA working was common and such cases were more likely to: lack contraception, need health adviser input, have a social worker and mental health problems highlighting an opportunity for closer working with mental health services.